A case of late-onset central hypoventilation syndrome with hypothalamic dysfunction: through a new phenotype - Onal, Hasan; Ersen, Atilla (The Turkish Journal of Pediatrics, 2010)
Congenital central hypoventilation syndrome (CCHS) is a rare disorder with uncertain nosology that usually presents early in life. The syndrome is characterized by ventilatory response impairment to carbon dioxide and may result in respiratory failure at birth. Recent reports have identified a similar clinical presentation beyond infancy called late-onset central hypoventilation syndrome (LO-CHS) as a disease continuum of CCHS with similar and overlapping pathophysiology. However, some have proposed that the syndrome accompanied by hypothalamic dysfunction (HD) be classified as a distinct clinical entity, LO-CHS/HD. To the best of our knowledge, the case reported herein is the oldest case of LO-CHS/HD in childhood, at 13 years old. He suffered from recurrent pulmonary edema, acute convulsive seizures, hypersomnia, hyperphagia, obesity, impaired glucose tolerance test, and hypercapnia, diagnosed as LO-CHS/HD, and was successfully treated with nasal bi-level positive airway pressure.